(untitled) (Journal of the Medical College for Women & Hospital, 2026)
Background: Enterobacter spp. are important emerging causes of nosocomial and community-acquired infections. Biofilm formation is an important virulence factor of Enterobacter spp. Formation of biofilm by Enterobacter spp. often results in multidrug-resistant chronic infections. Aim: This study was conducted to phenotypically determine biofilm formation in Enterobacter spp. isolates from different clinical specimens and to correlate biofilm formation with the antimicrobial resistance pattern of the isolated Enterobacter.Materials and Method: This cross-sectional study was conducted in the Department of Microbiology of BSMMU, Dhaka, Bangladesh, from September 2018 to July 2019. A total of 50 laboratory isolates of Enterobacter from different clinical specimens were collected and evaluated phenotypically for biofilm formation by the tissue culture plate method. The isolates were also tested for antimicrobial susceptibility testing by Kirby- Bauer disc diffusion method and evaluation of resistance pattern between biofilm producer and non-producer isolates was done.Results: Among the 50 Enterobacter isolates, 32 (64%) were found as biofilm producers phenotypically. Regarding antimicrobial resistance, resistance rates were higher in biofilm producers compared to non-biofilm producing isolates of Enterobacter. Relatively higher resistance rates were observed in the Cephalosporin group of antibiotics. Resistance rates to cefoxitin, cefixime, cefuroxime, and ceftazidime were 81%, 66%, 63% and 50% respectively in biofilm-producing isolates, whereas in non-biofilm producers, the resistance rates were 72%, 50%, 33% and 33% respectively. Relatively lower resistance was found to gentamicin, amikacin, netilmicin, meropenem, and piperacillin-tazobactam.Conclusion: Biofilm formation is a major virulence factor of Enterobacter spp. that plays a vital role in pathogenesis and also resistance to antimicrobial agents. Detection of biofilm by the tissue culture plate method can be introduced as a routine test in the laboratory. This would guide the physicians to prescribe appropriate antibiotics and to take other necessary measures to combat biofilm-related infections. J Med Coll Women Hosp.2026; 22(1): 116-123